Multimedia Pembelajaran Pada Mata Pelajaran Teknik Instalasi Tenaga Listrik (TITL) kelas X - Ismawati Ismawati; Juhaidatur Rahmi; Johan Eka Wijaya DN; Joko Kuswanto (Komputer dan Pembelajaran, 2025)
This research aims to develop learning multimedia in the subject of Electrical Power Installation Engineering (TITL) class X at Vocational High Schools (SMK). The research method used is Research and Development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The results of validation by experts show that the multimedia product developed is very feasible to use with the criterion of "Excellent". As for the entire recapitulation for the field trial, the eligibility criteria were obtained "Very Good". Thus, this learning multimedia is declared valid and effective as a supporting medium in TITL learning, bridging the gap between theory and practice